OPTIMASI DESAIN GENERATOR PHOTOVOLTAIK-DIESEL BERDASARKAN LAJU PENANGKAPAN IKAN DAN LIFE CYCLE COST, STUDI KASUS BAGAN PERAHU 10 GT DI PERAIRAN SAMATE PEMDA RAJA AMPAT, PAPUA BARAT - Akhmad Nurfauzi; Sardono Sarwito; Sutopo Purwono Fitri (Jurnal Airaha, 2018)
Utilization of Gen-set Hibrid Photovoltaik-Diesel (DC-AC Couple Battery-Backup Grid Connecting PV System) is a efforts to minimization operational cost from Stick held dipnet. This case is caused by diesel fuel which has higher price and rare. This article will discuss about analysis approach as first, calculate impact need of lighting toward rate of catching phototaxis fish. This case use analysis different test (test of t) toward output of optimum catching use 4 underwater lamps which have different of kind. The porpose from this case to analysis genset diesel capacity by usage optimum power of lighting. The method will be used is calculating instrumentation load factor, synchronic factor, and load of genset factor as standart of BKI. Based on monitoring, selected under water lamp E-CDL 45 W is real different (tcalculate3,4355>ttable2,776) which has more optimum catching of fish (6960 Kg) than others. Based on calculating needed daily load capacity 2530 W. It mean the capacity of Genset Hibrid PV array-Diesel 34020 Wh, appropriate with Samate water condition which has low and high temperature (27,1o C and 31,8o C) needed 15 PV-modul @200 W (the voltage and electric current source of PV array 100 Vdc and 31,6 A), bank battery 14 units @200 AH/12 V which has output voltage is 24 Vdc, 2 units charge controller (@current input 15 A), 1 unit inverter (voltage input 24 Vdc/output 240 Vac and 3000W), battery charger (input 240 Vac/output 24 Vdc), and MCB (standby load : single phase 220 Vac) 15 A Busbar 45 A. Ecomonic analysis use Life Cycle Cost (LCC) method toward genset (diesel and Hibrid PV array-diesel). From the calculating, nominal of LCC genset Hibrid PV array-Diesel (Rp.173.421.297,-) lower or cheaper than LCC genset diesel (Rp.223.715.493,-). The net from this case is Rp.50.294.196,- which got for 20 years instrumentations usage. The last discuss about calculating distance between stick held dipnet and area which can reached to outside lighting lamp (E-CDL 50 W) at height 5 meters toward surface of sea water is 235 m2.